Ultra Short Term Power Prediction of Offshore Wind Power Based on Support Vector Machine Optimized by Improved Dragonﬂy Algorithm - Yu, Yanxia; Wu, Yingshuai; Zhao, Liang; Li, Xiang; Li, Yanan (Distributed Generation & Alternative Energy Journal, 2021)
In order to improve the prediction effect of ultra short term power of offshore wind power, the prediction model based on support vector machine optimized dragonﬂy algorithm is constructed. Based on summary of the prediction methods of wind power, the support vector machine optimized by dragonﬂy algorithm is established. Finally, prediction simulation analysis of offshore wind power is carried out, results show that the proposed prediction model in this research can effectively improve the computing prediction precision.